Pathophysiology of humeral fractures in a sample of dairy heifers. Issue 4 (3rd July 2016) - Dittmer, KE; Hitchcock, B; McDougall, S; Hunnam, JC
Abstract: AIMS: To investigate the pathophysiology of humeral fractures in first-lactation dairy heifers in the North Island of New Zealand. METHODS: Ten 2-year-old dairy heifers with humeral fractures were subject to euthanasia and the fractured and non-fractured contralateral humeri were collected. Humeri were also collected from 10 unaffected 2-year-old dairy heifers sent for slaughter. Humeri from heifers with and without fractures were examined using computed tomography (CT), and four slices of the diaphysis and lower metaphysis (D1–4) were analysed using the Bone J plug-in for Image J. The humeri were sectioned sagittally and 5 mm bone slabs were processed for histopathology. RESULTS: There were no differences in bone length between the humeri from heifers with or without fractures (p=0.31). Median cortical bone mineral density at D1 was increased in humeri from affected compared with unaffected heifers (810 vs . 783 mg/cm 3 ; p=0.03), cortical area at D1 was reduced (816 vs . 1, 037 mm 2 ; p=0.04), the median stress strain index, a calculated theoretical measure of bone strength, at D1 was decreased (7, 288 vs . 9, 072 mm 3 ; p<0.01), and the median ratio of overall bone volume (BV) to total volume (TV) was decreased (0.32 vs . 0.38; p<0.01). The median periosteal circumference at D1 was also reduced in humeri from affected compared with unaffected heifers (151 vs. 173 mm; p<0.01). Using a binary logistic regression model, BV/TV was the only variable associated with humeral fractures (p=0.03).In nine of 10 fractured humeri the fracture appeared to have started just distal to the head of the humerus and spiralled distally down the diaphysis to end just above the humeral condyles. Histopathological findings included a reduction in the number, and thickness, of trabeculae in the metaphysis; metaphyseal growth arrest lines, and osteoclastic resorption in fractured humeri. Concentrations of copper in serum from four of five animals with fractures were within, and one was below, normal reference ranges, while concentration of copper in the livers of three heifers with fractures were below adequate ranges. CONCLUSIONS: The CT and histological findings were consistent with a diagnosis of osteoporosis. We propose that humeral fractures in dairy heifers are associated with osteoporosis, possibly as a result of insufficient deposition of bone during growth because of protein-calorie malnutrition. Increased osteoclastic resorption of bone associated with calcium mobilisation for lactation, and periods of copper deficiency may contribute to bone weakening.